Diagnosis and management challenges in patients with mild haemophilia A and discrepant FVIII measurements. (12th February 2014) - Trossaert, M.; Lienhart, A.; Nougier, C.; Fretigny, M.; Sigaud, M.; Meunier, S.; Fouassier, M.; Ternisien, C.; Negrier, C.; Dargaud, Y.
Summary Thirty per cent of patients with mild haemophilia A (MHA) present markedly different FVIII: C level when assayed by one‐stage clotting and two‐stage chromogenic assays. It is, therefore, a real clinical challenge to predict the individual bleeding risk of these patients. The aim of the present work was to study the relationship between the bleeding tendency of these patients with the results of a panel of phenotypic and genotypic tools. Thirty‐six patients with MHA were included in this multicentre prospective clinical study. The severity of bleeding symptoms was evaluated using the ISTH/SSC score. FVIII:C levels were measured using an activated partial thromboplastin time‐based one‐stage FVIII assay (FVIII: C1) and three commercial chromogenic kits (FVIII:CR). FVIII antigen levels, thrombin generation measurement and FVIII gene mutation analysis were also performed. Our results showed that a one‐stage FVIII: C assay cannot rule out the diagnosis of MHA, a combined use of FVIII:C1 with a FVIII:CR is suitable for detecting MHA. We observed that FVIII:CR results better reflected the clinical bleeding tendency of patients compared to FVIII:C1. We also observed a relationship between thrombin generation (TG) capacity and FVIII:CR of these patients. FVIII gene mutation analysis showed mutations previously reported in MHA patients with discrepant FVIII:C measurements, but with no predictive value of the individual bleeding phenotype of patients. Overall, we observed a relationship between chromogenic FVIII:C results, TG assay and bleeding tendency of patients with discrepant FVIII:C measurements, while FVIII:C1 was not well correlated with clinical bleeding phenotype in this particular population.